2005
DOI: 10.1097/01.mlr.0000182490.09539.1e
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Services After the Implementation of the Nursing Home Prospective Payment System

Abstract: The implementation of the PPS in nursing homes has been associated with a decrease in the amount of rehabilitation services, targeted at those predicted to receive higher amounts and an increased frequency of providing services targeted at those predicted to be less likely to receive them. The outcomes of the changes deserve further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The prospective payment system and diagnosis related groups for acute hospitals and the post-acute sector led to shorter hospital lengths of stay with subsequent increases in post-acute care health utilization and costs during the 1990s 19, 20, 33, 34. While the numbers of patients with medical illnesses receiving post-acute physical, occupational, or speech services has increased in skilled nursing facilities, rehabilitation hospitals, and long-term care hospitals, the amount of rehabilitation received by patients has decreased in some settings and remains of short duration (<1 month) 19, 20, 35-37. Little is known about the functional consequences of these utilization changes to older medical patients, or the best way to cost-effectively deliver high quality care that maximizes functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prospective payment system and diagnosis related groups for acute hospitals and the post-acute sector led to shorter hospital lengths of stay with subsequent increases in post-acute care health utilization and costs during the 1990s 19, 20, 33, 34. While the numbers of patients with medical illnesses receiving post-acute physical, occupational, or speech services has increased in skilled nursing facilities, rehabilitation hospitals, and long-term care hospitals, the amount of rehabilitation received by patients has decreased in some settings and remains of short duration (<1 month) 19, 20, 35-37. Little is known about the functional consequences of these utilization changes to older medical patients, or the best way to cost-effectively deliver high quality care that maximizes functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Current rehabilitative utilization patterns suggest that many medical patients with functional decline are not receiving the most aggressive short-term intervention available. Possible explanations include inability to meet functional requirements or the requirement that 75% of admissions to inpatient rehabilitation facilities be for specific categorical diagnoses 19, 20, 35-37. It is not known who with medical illness is most likely to benefit from acute rehabilitation, or whether care through home care, skilled nursing facilities, or rehabilitation hospitals would be most likely to improve outcomes 44, 45.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this resulted in a greater number of patients receiving rehabilitation therapy, but a general decrease in the amount of therapy given in hours per week. However, nursing home patients with medical diagnoses including MS received more care [15] . Also, in 1996, the immunomodulatory drugs interferon-␤ 1a and glatiramer acetate were approved by the FDA as subcutaneous injections, providing more out-of-hospital treatment options [16] .…”
Section: Discussionmentioning
confidence: 99%
“…7,21 Murray et al 21 found that the proportion of people receiving therapy increased between 1994-1996 and 2001, but the hours of therapy decreased slightly. This finding was condition specific, as people with medical conditions received the largest increase in rehabilitation services and those with stroke experienced the greatest decline.…”
Section: Discussionmentioning
confidence: 99%